(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The purpose of this article is to offer a view on the subject of the role of the information and communication technologies in the distribution channels with in the area of logistics and the supply chain management, all of the foregoing in a context where retailers are gradually becoming more concentrated and more powerful before manufacturers. In this situation, a closer cooperation between manufacturers and retailers will take place in order to provide a more efficient response to the consumer and reduce costs, and also to form stable medium and long term mutual cooperation relationships.To achieve this objective, the implementation of information and communication technologies by the companies will be required.